Involving customers in innovation: knowledgeability and agency as process variables - Peters, Linda D.; Pressey, Andrew D.; Gilchrist, Alan; Johnston, Wesley J. (Emerald, 2018)
Purpose: Recent research places an increased emphasis on the inclusion of the customer in value creation, learning, and innovation processes yet there remains a gap in our understanding of just how such customer involvement may work. This paper seeks to address this gap by examining two aspects of customer involvement; their knowledgeability and their agency. In addition, we explore three boundaries (semantic, syntactic, and pragmatic) across which relationship development occurs and which mayfacilitate and/or inhibit value co-creation, collaborative learning, and innovation processes. Design/methodology/approach: We utilised three case studies. Two were large scale construction projects in the UK, and one was a global professional accounting firm in the USA. Findings: Customers may become frustrated if not allowed to exercise their agency. However, their involvement can create tensions for suppliers who may have to become more tolerant of divergent goals. In respect of knowledgeability, we found that constraint satisfaction is important in allowing customers to reconcile their personal knowledge schema with that of the collective schema. However, we also noted that customer knowledgeability brings with it challenges for suppliers, who must find ways to add value for such customers. Research implications: We pose a number of further questions relating to the agency and knowledgeability of customers and their inclusion in value co-creation, collaborative learning, and innovation processes. We also highlight the need for guidance in identifying and minimising the barriers to crossing semantic, syntactic and pragmatic boundaries between customers and suppliers. Originality/value: We make an important contribution to research in the field in that we investigate how the inclusion of the customer in business networksalters current assumptions and practices.